2020
DOI: 10.1007/s10653-020-00677-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally safe release of plant available potassium and micronutrients from organically amended rock mineral powder

Abstract: The staggering production of rock dusts and quarry by-products of mining activities poses an immense environmental burden that warrants research for value-added recycling of these rock mineral powders (RMP). In this study, an incubation experiment was conducted to determine potassium (K) and micronutrients (Zn, Cu, Fe and Mn) release from a quarry RMP to support plant nutrition. Four different size fractions of the RMP were incubated with organic amendments (cow dung and legume straw) under controlled conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 61 publications
(79 reference statements)
2
19
0
1
Order By: Relevance
“…Table 3 was indicated that incremental levels of zinc showed nonsignificant increase on available status of potassium over control (Zn0) during both the years. These findings are enline to the findings of Ranpriya et al [26] and Basak et al [27].…”
Section: Zinc On Available Potassiumsupporting
confidence: 89%
“…Table 3 was indicated that incremental levels of zinc showed nonsignificant increase on available status of potassium over control (Zn0) during both the years. These findings are enline to the findings of Ranpriya et al [26] and Basak et al [27].…”
Section: Zinc On Available Potassiumsupporting
confidence: 89%
“…Biotite is a faster-release K silicate source than K-feldspar (Mohammed et al 2014), and this may be strategic in the management of these sources, in relation to the residual effect. Rocks with these minerals are common in many countries and can be used as a model for studying the behavior of silicate minerals with potential to provide K for agriculture (Basak et al 2020).…”
Section: Abstract Resumomentioning
confidence: 99%
“…They are formed by tetrahedral silica and aluminum groups, strongly linked together by cations, with the K inserted in the crystalline structure, making it difficult to extract (12). As a consequence, the dissolution process of this mineral in the soil involves complex reactions and mechanisms, which limits its application as a natural fertilizer once it does not meet the minimum nutritional demands required by plants (21,22). A better understanding about the action of microbial organic acids on highly available minerals such as K-feldspar could contribute to promote their use as natural fertilizer.…”
Section: Introductionmentioning
confidence: 99%